On the Extended Notion of Material Homogeneity - Epstein, M. (Technische Mechanik - European Journal of Engineering Mechanics, 2019)
The theory of continuous distributions of inhomogeneities is shown to be applicable beyond its original context, to certain classes of material bodies that are not necessarily uniform.